2017
DOI: 10.1039/c7ob01266g
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective [3 + 2] cycloaddition of 3-ylideneoxindoles with in situ generated CF2HCHN2: syntheses of CF2H-containing spirooxindoles

Abstract: An efficient [3 + 2] cycloaddition of 3-ylideneoxindoles with in situ generated CFHCHN for the syntheses of spirooxindoles has been developed. This methodology gives access to a range of relatively complex spirooxindoles featuring a CFH group and three contiguous stereogenic centers in up to 84% yield and 99 : 1 trans/cis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…The 4, 5-dihydro-3H-pyrazole ring adopts an envelope conformation with C9 atom deviating by 0.3474(3) Å from the plane formed by C1, C10, N1 and N2 for Mole1, C9A atom deviats by 0.3816(2) Å from the plane formed by C1A, C10A, N1A and N2A for Mole2 [15]. The bond lengths and angles of indolin-2-one and 4,5-dihydro-1H-pyrazole ring are similar to those found in literature [16][17][18]. The indolin-2-one ring and 4,5-dihydro-3Hpyrazole ring form spiro structural feature through their third atom (C1).…”
Section: Commentsupporting
confidence: 82%
“…The 4, 5-dihydro-3H-pyrazole ring adopts an envelope conformation with C9 atom deviating by 0.3474(3) Å from the plane formed by C1, C10, N1 and N2 for Mole1, C9A atom deviats by 0.3816(2) Å from the plane formed by C1A, C10A, N1A and N2A for Mole2 [15]. The bond lengths and angles of indolin-2-one and 4,5-dihydro-1H-pyrazole ring are similar to those found in literature [16][17][18]. The indolin-2-one ring and 4,5-dihydro-3Hpyrazole ring form spiro structural feature through their third atom (C1).…”
Section: Commentsupporting
confidence: 82%
“…The authors conducted this transformation in different solvents, and demonstrated the compatibility of the in situ preparation of CF 2 HCHN 2 with dichloromethane, chloroform, and acetonitrile. [31] The authors subjected the pyrazoline product to at hermal elimination of nitrogen, which resultedi nf ormation of CHF 2 -spirocyclopropanes (29, 30)i na highly diastereoselective manner.B iological testing of CHF 2 -cyclopropanes with differenth uman cancerc ell lines showed a Scheme5.Dipolar [3+ +2]-cycloadditions of CF 2 HCHN 2 (2)w ith alkynes.…”
Section: (A) Dipolar [3+ +2]-cycloaddition Reactionsmentioning
confidence: 99%
“…2019, 25,6053 -6063 www.chemeurj.org marked cytotoxic effect, which was in as imilara ctivity range compared to cis-platin. [32] An interesting reaction was observed by the same authors when switching from dichloromethane to diethyle ther as as olventi na no xygen atmosphere.C F 2 HCHN 2 (2)i nitially underwent dipolar [3+ +2]-cycloaddition to form a pyrazoline that participated in an oxidative [1,5]-sigmatropic rearrangement, followed by a1 ,2-hydrogen shift and dehydrogenationt oy ield pyrazolo[1,5-c]quinazolines (31,32)i ng ood to excellent yields (Scheme8). [33] Recently,W ua nd co-workerss tudied the reactiono fi ns itu generated CF 2 HCHN 2 (2)w ith N-substituted maleimides.…”
Section: (A) Dipolar [3+ +2]-cycloaddition Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the examples reported in the preceding paragraph concern a chiral molecule containing an N -CHF 2 substituent. There are many examples of azoles bearing a C -CHF 2 substituent, mainly in agrochemistry [ 31 , 32 , 33 ], the field of N -CHF 2 and N -CRF 2 azoles is less studied although there are several articles dealing with the structures presented in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%